ANALYTICAL SURVEY OF MACROECONOMIC INFLUENCES ON LOCAL BUDGET REVENUES IN UKRAINE - Kotina , H. M.; Stepura , M. M.; Tilichenko, Ye.H. (The actual problems of regional economy development, 2020)
The purpose of the paper was to examine the main factors determining the spatial structure and time dynamics of local budget revenues, highlight the major trends which lead to changes in the considered financial indicators, and construct a multi-factor model of the dependence of budget revenues from other economic indicators. The article highlights the economic and social value of local budget revenues in terms of decentralization and European integration of Ukraine. The main trends and factors which have an influence on the amount of financial resources of local governments in Ukraine are determined. A multi-factor model for variation of budget revenues under the influence of external and internal factors has been constructed. The results of the study will be used in the further work during the process of developing of specific proposals on how to increase the efficiency of exploitation of public financial resources.